2015
DOI: 10.3389/fpsyg.2015.00427
|View full text |Cite
|
Sign up to set email alerts
|

Dietary self-control influences top–down guidance of attention to food cues

Abstract: Motivational objects attract attention due to their rewarding properties, but less is known about the role that top–down cognitive processes play in the attention paid to motivationally relevant objects and how this is affected by relevant behavioral traits. Here we assess how thinking about food affects attentional guidance to food items and how this is modulated by traits relating to dietary self-control. Participants completed two tasks in which they were presented with an initial cue (food or non-food) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Moreover, it was not differentiated if dieters were successful or unsuccessful. In a recent study, it could be shown that successful dieters’ reaction times were less affected by food cues in a working memory task, indicating that dieting success may indeed moderate food cue-related working memory performance (Higgs et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was not differentiated if dieters were successful or unsuccessful. In a recent study, it could be shown that successful dieters’ reaction times were less affected by food cues in a working memory task, indicating that dieting success may indeed moderate food cue-related working memory performance (Higgs et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Participants identified the target faster while memorising food stimuli compared with non-food stimuli. This suggests that thinking about food is potentially associated with lower cognitive load than thinking about non-food stimuli [5,6,[13][14][15]. We also showed a stronger validity effect to food items.…”
Section: Introductionmentioning
confidence: 52%
“…Across several behavioural studies, we showed that holding foodrelated information in working memory biases attention to food stimuli (e.g. [5,13]). Participants identified the target faster while memorising food stimuli compared with non-food stimuli.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a recent study, a similar task was used in combination with the TFEQ disinhibition scale and an attentional bias to energy dense food was again reported to be largest in the group high in disinhibition [21]. Furthermore, it was shown that the tendency towards disinhibited eating was associated with greater attention to food versus non-food pictures in a priming and working memory task [22]. The aim of our study was to explore how individual disinhibition scores modulate attentional networks in the presence of food stimuli not only on the behavioral, but also on the neuronal level.…”
Section: Introductionmentioning
confidence: 99%